1988
DOI: 10.1159/000234608
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Rye Pollen <i>(Secale cereale)</i> Allergens Using Patients’ IgE, Immunoprint, Western Blot and Monoclonal Antibodies

Abstract: Rye pollen (Secale cereale) was investigated by Immunoprint and Western Blot analysis. Using Immunoprint, more than 30 proteins could be shown to be allergens in terms of their IgE binding, and 9 were determined as major allergens. In Western Blot 17 allergens were discovered, 3 of them major allergens. 4 monoclonal antibodies raised against a pollen extract of 6 grasses showed cross-reactivity to rye pollen, thus indicating common epitopes. 1 of 3 monoclonal antibodies produced against an extract of rye polle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

1989
1989
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
(43 reference statements)
1
7
0
1
Order By: Relevance
“…Studies performed with murine monoclonal antibodies also demonstrated the strong cross-reactivity between protein extracts made from S. cereale, but also Festuca rubra, L, perenne, P. pratensis, P. pratense, D. glomerata and A. odoratum [15]. These results confirm the high antigenic similarity between these species, as can be anticipated from their close phylogenetic relationship.…”
Section: Molecular Immunologysupporting
confidence: 73%
“…Studies performed with murine monoclonal antibodies also demonstrated the strong cross-reactivity between protein extracts made from S. cereale, but also Festuca rubra, L, perenne, P. pratensis, P. pratense, D. glomerata and A. odoratum [15]. These results confirm the high antigenic similarity between these species, as can be anticipated from their close phylogenetic relationship.…”
Section: Molecular Immunologysupporting
confidence: 73%
“…The NC was blocked with 0-1 "/o Tween. cut in strips and incubated with patient sera as described by Westphal [9]. For detection ofspecific IgE and IgG, an alkaline phosphatase linked 2nd goat-anti-human antibody (DIANOVA) was used.…”
Section: Treatmentmentioning
confidence: 99%
“…These allergenic determinants are the sites to which the IgE antibody is produced. More precise information concerning the clinical relevance of these al lergenic determinants may be obtained by using purified proteins [9][10][11],…”
Section: Introductionmentioning
confidence: 99%